A social network comparison between a Classroom-as-Organization and traditional management classes. Issue 8 (16th November 2020) - Cocieru, Ovidiu C.; Katz, Matthew; McDonald, Mark A.
Abstract: The constructivist theory of learning states that student interaction with peers leads to cognitive development. Meanwhile, scholars claimed that traditional management classes that use group work do not promote student interaction effectively. Despite this concern, student interaction has not been compared between different courses. In the current study, the authors used social network analysis to explore student interaction in two traditional classes and one that followed the Classroom-as-Organization (CAO) approach. The authors found that the CAO involves students in a better cohesive network of interactions compared to other classes. Implications for management educators are discussed.